2011
DOI: 10.1007/s11251-011-9167-4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting self-regulated hypermedia learning through prompts

Abstract: The aim of this research was to develop and evaluate tools and supports for self-regulated learning with hypertext information structures, such as Web pages. Two kinds of supports for self-regulated learning were developed and tested experimentally: Prompting and Prompting with Training. In Experiment 1, Prompting was tested with a pre-post-test between subject design, including thinking-aloud data. Students of the experimental group (n = 20) were prompted for self-regulation activities that had to be followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 41 publications
6
124
1
7
Order By: Relevance
“…However, this effect is less likely to occur in less structured domains (Nievelstein, van Gog, van Dijck, & Boshuizen, 2013), which, in combination with the low pretest scores, makes it unlikely that an expertise reversal effect occurred. The other method of support, prompting, can be ineffective when prompts are not used as intended, in which case they show reduced effects on learning outcomes and reported mental effort (Bannert & Reimann, 2011). Although answers to the prompts were generally short (i.e., approximately one sentence), they indicated that the prompts were used as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect is less likely to occur in less structured domains (Nievelstein, van Gog, van Dijck, & Boshuizen, 2013), which, in combination with the low pretest scores, makes it unlikely that an expertise reversal effect occurred. The other method of support, prompting, can be ineffective when prompts are not used as intended, in which case they show reduced effects on learning outcomes and reported mental effort (Bannert & Reimann, 2011). Although answers to the prompts were generally short (i.e., approximately one sentence), they indicated that the prompts were used as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…It is already established that effective learning depends on the nature and sequencing of self-regulated activities by the learner (Bannert & Reimann, 2012); and although self-regulation skills and learning strategies are needed for any educational context, they are more important in a technology-enhanced learning environment (Lin, Hmelo, Kinzer, & Secules, 1999). In MOOCs, where there is no guidance or support from an instructor, and the course is not structured around classes, learners' ability to selfregulate their own learning process is especially relevant (Hood et al, 2015;).…”
Section: Self-regulated Learning Strategies In Moocsmentioning
confidence: 99%
“…Pedagogical tools can vary from being relatively short-time reminders (e.g. pop-up windows that prompt the user) to goal-setting and planning tools that depend on the learning phase (Bannert and Reimann 2012). In addition, these tools can be relatively stable, and they are available throughout learning; learners can choose when and how to use the tools provided (Perry and Winne 2006).…”
Section: Traditions For Supporting Social and Cognitive Performance Imentioning
confidence: 99%